International transmission of U.S. monetary policy and its determinants. - Lin, Zhanyi. (2009)
This paper investigates the transmission of changes in U.S. monetary policy to other countries’ interest rates. More specifically, we examine the extent to which changes in the U.S. Federal Funds rate affect the monthly average one-month interbank rates of other countries, in short, the degree of pass-through. Long- and short-term pass-through coefficients of 48 countries are estimated from the period of 1980 to 2008. The long-term pass-through coefficients are then analyzed against 10 macroeconomic factors (GDP growth, GDP per capita, trade balance, external debt, inflation, bank concentration, size of banking sector, size of capital markets, flexibility of exchange rate regimes and whether the country’s currency is pegged to the U.S. dollar) to identify the determinants of passthrough. Our results revealed that the interbank rates of five countries are independent of changes in the Federal Funds rate, 27 countries had experienced incomplete pass-through and the rest encountered more-than-complete pass-through. In addition, we found that inflation was the only determinant of long-term pass-through. Countries experiencing higher levels of inflation are likely to have a lower degree of long-term pass- through, implying a tendency to set their own interest rates and consequently pursue a more independent monetary policy.